A service-based software architecture for enabling the electronic health record storage using Blockchain. (19th June 2021) - Lima, Ítalo; Araújo, André; Souza, Rychard; Couto, Henrique; Times, Valéria
The healthcare sector requires computational solutions with reliable authenticity features for the storage and retrieval of electronic health record data. To address this important issue, this article proposes a service-based software architecture to extract data from different legacy databases, standardise the patient's clinical data requirements and store data using different Blockchain technologies. To achieve this, a software architecture has been designed to guarantee the independence of data storage technology. In addition, a data meta-schema and a set of mapping rules have been specified to store and organise clinical data following an international health standard. To validate the solution presented, the real world scenario of a Brazilian healthcare institution has been used to evaluate the data extraction, standardisation and storage capabilities in two Blockchain platforms widely used in the information technology market.